Marketing Strategy to Improve the Competitiveness of Lurik Woven Fabric MSMEs Centers in Klaten, Central Java - S. Suranto; Much. Djunaidi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
Lurik